Strategi Implementasi Keselamatan Pasien untuk Meningkatkan Kualitas Pelayanan di RSUD Abdoel Wahab Sjahranie - Siti Wardatun Hasanah (Nusantara Innovation Journal, 2024)
Patient safety is a crucial aspect of hospital services that directly affects the quality of patient care. Many hospitals still face challenges in implementing effective patient safety. This study aims to analyze the influence of effective strategies in implementing patient safety to improve the quality of hospital services. Methodology: This research is explanatory research which aims to explain the influence of the relationship between the variables that have been determined. Respondents involved 90 PPAs from various service installations at Abdoel Wahab Sjahranie Hospital Samarinda, selected through a purposive sampling method. The research instrument is a validated questionnaire and data analysis was carried out using Structural Equation Modeling - Partial Least Square (SEM-PLS) version 4. Results: Patient Safety Implementation Strategy (X1) has a strong and significant effect on Service Quality (Y1) with a value (p = 0.000 < 0.05). The influence on compliance with safety procedures (Z1) shows an influence that is close to significant (p = 0.077), while the influence on customer satisfaction (Z2) shows a moderate influence that is close to significant (p = 0.063). Service quality (Y1) significantly mediates the effect of safety strategy on compliance with safety procedures (Z1) and customer satisfaction (Z2), with both p values ​​of \0.000 (< 0.05). Conclusion: A comprehensive and integrated patient safety implementation strategy can significantly improve the quality of hospital services.